Inovasi Pendidikan Berkarakter Menciptakan Generasi Emas 2045 - Sitti Hartinah; Lilis Patimah; Ahmad Faruk; Ferdi Zulkarnain; Budi Mardikawati; Singgih Prastawa (Journal on Education, 2024)
This journal explores the implementation of character education innovation as a key strategy in forming the Golden Generation 2045. The research uses a qualitative approach with case studies, focusing on changes in the curriculum, teaching methods, and the role of the school and family environment. The research results show that this innovation has a positive impact on the formation of student character, with an emphasis on values ​​such as honesty, responsibility, creativity and leadership. The teacher's role in developing teaching methods that encourage student character is central, with approaches such as group discussions, collaborative projects, and daily life simulations. Students show positive responses with increased understanding of character values ​​and ability to adapt to complex situations. The active role of parents in supporting this innovation has also proven to be significant, involving participation in school activities and the application of character values ​​at home. Although the research faces challenges in quantitative evaluation and a lack of support from some parents and teachers, the conclusions confirm the importance of character education innovation as a foundation for creating the Golden Generation 2045. Policy recommendations include increasing teacher training, the active role of parents, and the development of more appropriate evaluation methods. The implications support efforts to improve the quality of education towards a future vision supported by a generation that is superior in character and intellectually.